African experiences and alternativity in International Relations theorizing about security. (10th January 2022) - Danso, Kwaku; Aning, Kwesi
Abstract : The authors show how Eurocentrism and methodological whiteness in security studies excludes African experiences as they manifest through hybrid security orders. The article draws on postcolonial discourses to explore how the study of events and processes in Africa could advance IR scholarship. Abstract: Deconstructing International Relations (IR) episteme acknowledges its generation of power imbalances in security knowledge that relegate African experiences to the margins of global politics. Central to this process of relegation is a pervasive 'methodological whiteness', which, while eliding coloniality and racism, projects white experience as a universal perspective. Accompanying this Eurocentric bias has been the intrusive projection of the Weberian state as the most effective site for security governance and conflict prevention on a continent with states that are characterized by a hybridity of political orders, which deviate substantially from the ideal-type state that they seek to mimic. Not only has this resulted in disastrous policies in many parts of Africa, but critical questions arise as to the relevance of conventional IR and security studies as neutral sites for dispassionate knowledge production and policy-making on African security, thereby necessitating alternative perspectives. This article reflects on the ways in which IR and security studies have been responsible, in part, for the production of a racialized mode of security knowledge generation that obfuscates the security policies and experiences of people in African locales. It draws on insights from post-colonial discourses and the episteme of alternativity to explore how the study of events and processes in Africa in a theoretically conscious manner could advance IR scholarship as a whole. It contends that incorporating African experiences as they manifest through hybrid security orders can broaden the empirical base for IR theorizing about security since they offer another perspective outside the conventional western assumptions and experiences.